Komparasi Akurasi Global Posistion System (GPS) Receiver U-blox Neo-6M dan U-blox Neo-M8N pada Navigasi Quadcopter - firdaus firdaus; Ismail Ismail (Teknik Elektro Politeknik Negeri Padang, 2020)
Quadcopter UAV development is happening very rapidly. One of the most important in the navigation system is the hardware and software or the used algorithm. Improving the accuracy of Quadcopter positioning is one of the most popular topics in the UAV field. This position parameter is determined by the GPS module. GPS modules produce position and speed information with a high degree of precision, but these modules are vulnerable to interference. Thus, GPS signals are often lost. Moreover, GPS measurements also cannot meet the real-time requirements. Both GPS U-Blox variants, Neo-6M, and M8N become the main problem by testing which are more precise and consistent with the actual geographical position indicated by Google map. Data obtained from GPS receivers are parsed and converted to longitude and latitude coordinates by the ATmega328 IC microcontroller then combine with real-time data from RTC DS1370 and stored continuously in a 2 GB SD card. The transferred geographic coordinate data would be retrieved and converted to CSV format so that it can be plotted into a map. The test was conducted where the Neo-6M GPS receiver was carried out